Critical Discourse Analysis of Benyamin Netanyahu ICC Open Hearing Session and Radar JawaPos Statement on Israel-Palestine Conflict - Nur Laily Arifiyah; Nurranafi Syam Maella; Zulaikha Zulaikha (UIBU, 2024)
This study aimed to analyze the speech by Israeli Prime Minister Benjamin Netanyahu in response to the ICC arrest warrant against Israeli leaders.. This study took a qualitative method with critical discourse analysis based on Norman Fairclough's theory. The subject of the research was the speech by Israeli PM Benjamin Netanyahu taken from the YouTube channel Forbes Breaking News, posted on May 21, 2024, titled